Pengaruh Pola Kelekatan Terhadap Penggunaan Bahasa Ambigu Dalam Konflik Interpersonal Pada Mahasiswa Pendidikan Bahasa Indonesia - Adellia Novisa Safitri; Roely Ardiansyah; Agung Pranoto (Universitas Wijaya Kusuma Surabaya, 2026)
Attachment patterns are psychological factors formed since childhood and influence the way individuals communicate, especially in stressful situations such as interpersonal conflicts. This study aims to examine the influence of attachment patterns on the tendency to use ambiguous language in interpersonal conflicts among students of the Indonesian Language Education Study Program at Wijaya Kusuma University, Surabaya. A descriptive quantitative approach was used involving 39 active students in semesters 1 to 7 as samples obtained through the Slovin formula. The research instrument used a Likert scale (1–5) consisting of an attachment pattern scale (ECR-R, 13 valid items) and an ambiguous language scale (8 valid items). Data analysis was carried out using simple linear regression with the help of IBM SPSS version 22. The results showed a t-value of 4.810 with a significance of 0.000 < 0.05 and R Square = 0.385, which means that attachment patterns have a significant effect on the use of ambiguous language by 38.5%. Students with insecure attachments (anxious and avoidant) are more likely to use ambiguous language as an emotion regulation strategy in conflict. These findings extend psycholinguistic research by integrating the psychological dimensions of attachment into the analysis of language behavior.